High-load composite iodine positive electrode based on MXene electrochemical reaction regulator as well as preparation method and application of high-load composite iodine positive electrode

By using MXene electrochemical reaction regulator in zinc-iodine batteries to prepare high-load composite iodine positive electrode and thin zinc foil negative electrode, the problems of multiple iodide shuttle and low utilization rate of zinc-iodine batteries are solved, and zinc-iodine batteries with high energy density and cycle stability are achieved.

CN119601570AActive Publication Date: 2025-03-11SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411624044.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-11
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Zinc-iodine batteries are prone to dendrite growth, hydrogen evolution and corrosion problems during charging and discharging, and the conversion of I2/I- forms water-soluble polyiodide, resulting in deterioration of zinc negative electrode. At the same time, it is difficult for the prior art to achieve high iodine proportion, high-load iodine positive electrode and high-utilization zinc negative electrode, which limits the performance and application of the battery.

Method used

Using a high-load composite iodine positive electrode based on MXene electrochemical reaction regulator, a high-load composite iodine positive electrode without shuttle effect was prepared by blending MXene nanosheets, carbon materials and cellulose into a three-dimensional interconnected self-supported composite electrode film, and loading iodine active substances by electrolyte permeation method. At the same time, thin zinc foil is used as the negative electrode to achieve a high utilization rate zinc negative electrode.

Benefits of technology

Effectively inhibit the shuttle effect of multi-iodide, improve the kinetics of the iodine conversion reaction, achieve high iodine load and high zinc negative electrode utilization, and improve the energy density and cycle stability of zinc-iodine batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601570A_ABST
    Figure CN119601570A_ABST
Patent Text Reader

Abstract

The invention relates to a high-load composite iodine positive electrode based on an MXene electrochemical reaction regulator as well as a preparation method and application of the high-load composite iodine positive electrode. The high-loading-capacity composite iodine positive electrode comprises a porous self-supporting composite electrode film and an iodine active substance, wherein the porous self-supporting composite electrode film is formed by wrapping a carbon material with an MXene / cellulose network formed by mixing an MXene nanosheet, the carbon material and cellulose, and the iodine active substance is loaded on the porous self-supporting composite electrode film; wherein the iodine active substance comprises I <-> ions and I2; the MXene nanosheet is at least one of Ti < 3 > C < 2 > T < x >, Nb < 2 > T < x >, Mo < 2 > T < x > and V < 2 > T < x >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of zinc ion batteries, and specifically relates to a method for preparing a high-load zinc-iodine battery positive electrode, and in particular to a high-load composite iodine positive electrode based on a MXene electrochemical reaction regulator, and a preparation method and application thereof. Background Art

[0002] Zinc-iodine (Zn-I2) batteries are rich in raw materials (55 μg L in seawater). -1 ), relatively high discharge voltage (1.38V vs. Zn / Zn 2+ ) and a higher theoretical specific capacity (I2 / I - , 211mAh g -1 ), is one of the aqueous batteries with development potential. Despite this, zinc-iodine batteries face significant challenges in terms of Zn negative electrode and I2 positive electrode technology. First, during the charge and discharge process of mild aqueous zinc-ion batteries, the negative electrode will inevitably have thorny problems such as dendrite growth, hydrogen evolution and corrosion, which seriously limit the performance of the battery. In terms of the positive electrode, I2 / I - The conversion of I3 - , I5 - The polyiodides tend to migrate to the zinc anode and react chemically with metallic zinc, which consumes the active zinc and aggravates the degradation of the battery. Therefore, simultaneously solving the problems of poor zinc reversibility and the polyiodide shuttle effect is crucial for the development of advanced zinc-iodine batteries.

[0003] Although significant progress has been made in solving the problem of multi-iodide shuttling and improving the reversibility of zinc anode by developing new iodine-loaded cathodes, modifying separators, or electrolyte additives, the practical research of zinc-iodine batteries is still lacking. On the one hand, in order to limit the shuttling effect of multi-iodides as much as possible, the active iodine ratio and iodine loading of the I2 electrode are relatively low, generally less than 15 mg cm -2 , which would result in an area specific capacity of less than 2 mAh cm -2 , which is significantly lower than the typical value of commercial lithium-ion batteries (3 mAh cm -2 ), which restricts the practical application of zinc-iodine batteries. On the other hand, in order to meet the long-cycle stability of the battery, the utilization rate of the zinc negative electrode is often very low to compensate for the irreversible zinc loss during the cycle. However, a large excess of zinc negative electrode seriously reduces the overall energy density of the battery, affecting its practical application. Therefore, it is of great significance to simultaneously achieve a high iodine ratio, a high-load iodine positive electrode and a high-utilization zinc negative electrode to promote the practical application of zinc-iodine batteries. Summary of the invention

[0004] In order to improve the practical value of zinc-iodine batteries, the present invention provides a generally applicable high-load iodine positive electrode and a preparation method thereof (vacuum filtration + electrolyte infiltration) to prepare a high-load iodine positive electrode without a shuttle effect; at the same time, a thin zinc foil is used as the negative electrode, thereby realizing a zinc-iodine battery with a high utilization rate of zinc negative electrode and a high energy density.

[0005] In a first aspect, the present invention provides a high-load composite iodine positive electrode based on a MXene electrochemical reaction regulator, wherein the high-load composite iodine positive electrode comprises: a porous self-supporting composite electrode membrane of a carbon material wrapped by a MXene / cellulose network formed by a mixture of MXene nanosheets, a carbon material and cellulose, and an iodine active substance loaded on the porous self-supporting composite electrode membrane; wherein the iodine active substance comprises I - ions and I2; the MXene nanosheet is Ti3C2T x 、Nb2CT x 、Mo2CT x 、V2CT x At least one of .

[0006] The present invention self-assembles an electrochemical reaction regulator MXene, a physical adsorbent carbon material, and a binder cellulose into a three-dimensional (3D) interconnected self-supporting composite electrode film. Among them, the carbon material with a high specific surface area is used as a physical carrier of iodine active species, and cellulose is used as a binder, so that the MXene nanosheets and the carbon material can self-assemble into a three-dimensional (3D) interconnected self-supporting composite electrode film. The MXene nanosheet regulator can enhance conductivity, improve the chemical anchoring ability of iodine species, and accelerate the kinetics of iodine conversion reactions.

[0007] Preferably, the loading of MXene on the high-loading composite iodine positive electrode is 0.7-1.8 mg cm -2 The loading amount of the iodine active substance is 10 to 25 mg cm -2 .

[0008] In a second aspect, the present invention provides a method for preparing a high-load composite iodine positive electrode based on a MXene electrochemical reaction regulator, comprising: (1) mixing MXene nanosheets, carbon material and cellulose to obtain a mixed dispersion; (2) vacuum filtering and freeze-drying the mixed dispersion to obtain a self-supporting composite electrode membrane; (3) Using an aqueous solution containing an iodine active substance as a positive electrode electrolyte, dripping it onto the self-supporting composite electrode membrane, and drying it to obtain the high-load composite iodine positive electrode.

[0009] Preferably, the carbon material is at least one of activated carbon, carbon nanotubes, carbon fiber, and graphene; the cellulose is at least one of plant cellulose, bacterial cellulose, and microfibrillated cellulose. The carbon material has a high specific surface area and is used as a physical carrier of iodine active species. The cellulose acts as a binder, so that the MXene nanosheets and carbon materials can self-assemble into a three-dimensional (3D) interconnected self-supporting composite electrode film.

[0010] Preferably, in step (1), the mass ratio of the MXene nanosheets, the carbon material and the cellulose binder is (0.1-2):(5-10):(0.1-1).

[0011] Preferably, in step (2), the freeze-drying temperature is -20 to -30°C and the time is 5 to 7 hours.

[0012] Preferably, the self-supporting composite electrode membrane is a porous self-supporting electrode formed by wrapping a carbon material with a highly conductive MXene / cellulose mixed network formed by cellulose and MXene nanosheets.

[0013] Preferably, in step (3), in the positive electrode electrolyte, I - The ratio of ion to I2 concentration is (5-10):(1-5); The amount of the positive electrode electrolyte dripped onto the self-supporting composite electrode membrane is determined according to the size and thickness of the self-supporting composite electrode membrane.

[0014] Preferably, in step (3), the drying is carried out at room temperature, and the drying time is 6 to 20 hours.

[0015] In a third aspect, the present invention provides a zinc-iodine battery, which includes the above-mentioned high-loading composite iodine positive electrode, a zinc negative electrode, a battery separator, and an electrolyte.

[0016] Preferably, the thickness of the zinc negative electrode is 10-20 μm.

[0017] Preferably, the battery separator is at least one of a glass fiber separator, an aramid nanofiber separator, a non-woven fabric separator, a filter paper separator, and a polyolefin separator.

[0018] Preferably, the electrolyte is a mixed electrolyte containing ZnSO4 and Li2SO4; in the electrolyte, the concentration ratio of ZnSO4 to Li2SO4 is (10-20): (1-5).

[0019] Beneficial effects: (1) The high-load composite iodine positive electrode prepared by the present invention can effectively inhibit the shuttle effect of multiple iodides and improve the iodine conversion reaction kinetics; (2) The high iodine loading positive electrode prepared by the present invention can establish a strong chemical adsorption, and the loading of iodine active substances is as high as 15.33-23 mg cm -2 ; (3) The high iodine loading battery positive electrode prepared by the present invention and the 10-20 μm zinc foil are assembled into a zinc-iodine battery, which can reduce the corrosion of the thin zinc negative electrode by polyiodide, and realize a zinc-iodine full battery with a stable high zinc negative electrode utilization rate and high energy density; (4) The high-loading composite iodine positive electrode based on MXene electrochemical reaction regulator provided by the present invention can be applied to zinc-iodine batteries, lithium-iodine batteries and other power and energy storage batteries and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscopy (SEM) image of the MX-AB electrode film prepared in Example 1; Figure 2 This is a digital photo of the MX-AB electrode membrane prepared in Example 1; Figure 3 The weight changes of the MX-AB electrode film and the MX-AB@I cathode film prepared in Example 1 before and after iodine loading; Figure 4 The thermogravimetric curves of the MX-AB electrode film and the MX-AB@I cathode film prepared in Example 1 before and after iodine loading; Figure 5 The cross-sectional SEM image of the MX-AB@I positive electrode prepared in Example 1 and the corresponding element distribution image; Figure 6 Flow chart of preparing MX-AB@I positive electrode in Example 1; Figure 7 is a SEM image of the AB electrode film prepared in Comparative Example 1; Figure 8 are the electrical conductivities of the MX-AB and AB electrode films prepared in Example 1 and Comparative Example 1, respectively; Fig. 9 In-situ ultraviolet absorption spectrum test of the "cuvette" zinc-iodine battery assembled with the MX-AB@I and AB@I positive electrode films prepared in Example 1 and Comparative Example 1; Fig.10 The zinc-iodine batteries assembled with different iodine positive electrodes prepared in Example 1 and Comparative Examples 1-3 were tested at a current density of 0.1 A g -1 Long cycle and Coulomb efficiency when Fig.11 The zinc-iodine battery assembled with the MX-AB@I and AB@I positive electrodes prepared in Example 1 and Comparative Example 1 was -1 CV curve under conditions; Fig.12The zinc-iodine battery assembled with 1.5x-MX-AB@I and 1.5x-AB@I positive electrodes prepared in Example 2 and Comparative Example 4 was tested at 0.1A g -1 Long cycle test results under 3.5°C. DETAILED DESCRIPTION

[0021] To further explain the content, features and practical effects of the present invention, the present invention is described in detail below in conjunction with the embodiments. It should be pointed out that the modification method of the design of the present invention is not limited to these specific implementation methods. Without departing from the spirit and connotation of the design of the present invention, the equivalent replacement and modification made by those skilled in the art on the basis of reading the content of the present invention are also within the scope of the present invention.

[0022] In the present invention, MXene nanosheets, carbon materials and binder cellulose are blended, and a self-supporting composite electrode membrane is obtained by vacuum filtration; the iodine active substance I is added by electrolyte permeation method. - Ions and I2 are loaded onto the self-supporting electrode film to obtain a high-load composite iodine positive electrode. The high-load composite iodine positive electrode can effectively inhibit the shuttle effect of polyiodides and improve the kinetics of iodine conversion reactions. In the preparation method of the present invention, the role of vacuum filtration is to regulate the film thickness by the concentration of the suspension, and the electrode film can be prepared efficiently and uniformly. The electrolyte permeation method is an effective iodine capture technology that loads iodine active ions by impregnation.

[0023] In the electrolyte penetration method for loading active iodine ions, iodine active materials can be uniformly, quickly and effectively adsorbed on the electrode. This method allows precise control of the amount of iodine loaded on the electrode without causing loss of active substances. Relying on the iodine sublimation phenomenon, encapsulating iodine in an adsorption film by melt diffusion is also a conventional strategy. However, in this process, iodine is only bound to the surface of the adsorbate, and in subsequent charge and discharge tests, a large amount of iodine escapes through electrochemical reactions, resulting in capacity loss. Therefore, in achieving high iodine loading (greater than 5 mg cm -2 )In the preparation of positive electrode, the electrolyte penetration method is irreplaceable.

[0024] In the present invention, the combination of vacuum filtration and electrolyte permeation can significantly reduce the preparation time and improve efficiency. More importantly, the iodine-loaded membrane prepared by vacuum filtration has a considerable specific surface area, providing abundant adsorption sites for iodine loading by electrolyte permeation, thus achieving a stable high iodine-loaded positive electrode.

[0025] In the present invention, MXene is a new type of two-dimensional material with a layered structure, a large number of active metal atoms and abundant polar surface functional groups. The titanium metal center in the MXene electrochemical reaction regulator has the function of a Lewis acid site, which can establish a strong chemical adsorption with the polyiodide anion (Lewis base), thereby effectively fixing the polyiodide on the positive electrode and inhibiting its shuttle effect. In addition, due to its electronic conductivity and catalytic activity, the MXene electrochemical reaction regulator can reduce I2 / I - The overpotential and activation energy barriers in the conversion process can significantly improve the kinetics of the iodine conversion reaction. Furthermore, the strong chemical adsorption and promotion of iodine conversion kinetics of MXene electrochemical reaction regulators can also reduce the corrosion of polyiodide on the thin zinc negative electrode, thereby improving its reversibility and achieving a stable high zinc negative electrode utilization and high energy density zinc-iodine full battery.

[0026] In the present invention, MXene nanosheets, carbon materials and cellulose are mixed, and the flexible electrode obtained by vacuum filtration is used as a carrier membrane for iodine active substances. The MXene in the present invention not only provides high conductivity and improves the conversion kinetics of iodine, but also can adsorb iodine active substances through chemical action, increase the iodine loading, and inhibit the shuttle effect. Therefore, in the high-load iodine positive electrode provided by this study, the MXene electrochemical reaction modulator solves the problems of slow kinetics and multi-iodide shuttling of high-load zinc-iodine batteries under the synergistic effect of high conductivity and chemical adsorption, which is of great significance to the practical development of zinc-iodine batteries.

[0027] The following is an exemplary description of the preparation method of the high-load composite iodine positive electrode based on the MXene electrochemical reaction regulator provided by the present invention (such as Figure 6 shown).

[0028] Preparation of MXene nanosheets. The MXene nanosheets in the present invention can be prepared by fluorine-containing etching (Naguib M, Kurtoglu M, Presser V, Lu J, Niu J, Heon M, Hultman L, Gogotsi Y, Barsoum MW. Two-dimensional nanocrystals produced by exfoliation of Ti3AlC2. Adv Mater. 2011 Oct 4; 23 (37): 4248-53.), electrochemical etching (Yang S, Zhang P, Wang F, Ricciardulli AG, Lohe MR, Blom PWM, Feng X. Fluoride-Free Synthesis of Two-Dimensional Titanium Carbide (MXene) Using A Binary Aqueous System. Angew Chem Int Ed Engl. 2018 Nov 19; 57 (47): 15491-15495.), alkaline etching (Li T, Yao L, Liu Q, Gu J, Luo R, Li J, Yan X, Wang W, Liu P, Chen B, Zhang W, Abbas W, Naz R, Zhang D. Fluorine-Free Synthesis of High-Purity Ti3C2T x (T=OH, O) via Alkali Treatment. Angew Chem Int Ed Engl. 2018 May 22; 57(21): 6115-6119.), molten salt etching (Ghidiu M, Lukatskaya MR, Zhao MQ, Gogotsi Y, Barsoum MW. Conductive two-dimensional titanium carbide'clay' with high volumetric capacitance. Nature. 2014 Dec 4; 516(7529): 78-81.) and other methods are used to prepare MXene nanosheets. As an example, 1g of lithium fluoride is dissolved in 15mL of 9M hydrochloric acid, and 1g of MXene precursor (Ti3AlC2) powder is slowly added. After etching at 40°C for 48 hours, it is then centrifuged and washed 6 times to obtain multilayer Ti3C2T x Then, the multilayer Ti3C2T xThe suspension was dispersed in 50 mL of deionized water and subjected to ultrasonic treatment for 60 min. Finally, after centrifugation for 40 min, the dark green supernatant was collected to obtain the few-layer Ti3C2T x MXene nanosheets.

[0029] MXene nanosheets, carbon material and cellulose binder are mixed to obtain a mixed dispersion.

[0030] In an optional embodiment, the MXene nanosheet is Ti3C2T x 、Nb2CT x 、Mo2CT x 、V2CT x The carbon material is at least one of activated carbon, carbon nanotubes, carbon fibers, and graphene. The cellulose binder is at least one of plant cellulose, bacterial cellulose, and microfibrillated cellulose.

[0031] In an optional embodiment, the mass ratio of the MXene nanosheets, the carbon material and the cellulose binder is (0.1-2): (5-10): (0.1-1), for example, 1:8:0.85. If the content of the MXene nanosheets is too little, it cannot adsorb enough polyiodides, resulting in the shuttle effect of polyiodides; if the content of the MXene nanosheets is too much, the adsorption force on iodine is too strong, and some iodine will lose its activity due to adsorption.

[0032] The mixed dispersion is subjected to vacuum filtration and freeze-drying treatments, and then cut by a slicer to obtain a self-supporting composite electrode membrane.

[0033] The positive electrode electrolyte is dripped onto the self-supporting composite electrode membrane by an electrolyte infiltration method to obtain the high-load composite iodine positive electrode. Specifically, an aqueous solution containing an iodine active substance is used as the positive electrode electrolyte, which is dripped onto the self-supporting composite electrode membrane and dried to obtain the high-load composite iodine positive electrode.

[0034] In an optional embodiment, in the electrolyte, I - The ratio of the concentration of ions to that of I2 is (5-10):(1-5). The amount of the electrolyte used is determined according to the size and thickness of the self-supporting composite electrode membrane.

[0035] In an optional embodiment, the drying is room temperature drying, and the drying time is 6 to 20 hours.

[0036] The loading of MXene on the high-loading composite iodine positive electrode prepared by the present invention is 0.7-1.8 mg cm -2 The loading of iodine active substances is 10-25 mg cm -2 .

[0037] In addition, the present invention also provides a zinc-iodine battery, which includes the above-mentioned high-loading composite iodine positive electrode, a zinc negative electrode, a battery separator, and an electrolyte.

[0038] In an optional embodiment, the thickness of the zinc negative electrode is 10-20 μm. As an example, a zinc sheet with a thickness of 10-20 μm is taken, polished, and then cut into a negative electrode sheet.

[0039] In an optional embodiment, the battery separator is at least one of a glass fiber separator and an aramid nanofiber separator.

[0040] In an optional embodiment, the electrolyte is a mixed electrolyte containing ZnSO4 and Li2SO4.

[0041] The following is an exemplary description of the assembly method of the zinc-iodine battery provided by the present invention.

[0042] Dissolve zinc sulfate and lithium sulfate in deionized water, stir, and prepare a mixed electrolyte of ZnSO4 and Li2SO4; assemble a positive electrode sheet, a negative electrode sheet, an electrolyte, and a battery separator into a zinc-iodine battery.

[0043] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0044] Example 1

[0045] The preparation process of the high-load composite iodine positive electrode based on the MXene electrochemical reaction regulator in Example 1 includes: (1) dissolving 1 g of lithium fluoride in 15 mL of 9 M hydrochloric acid, slowly adding 1 g of MXene precursor (Ti3AlC2) powder, etching at 40° C. for 48 hours, and then washing by centrifugation 6 times to obtain a multilayer Ti3C2T x Then the multilayer Ti3C2T x The suspension was dispersed in 50 mL of deionized water and subjected to ultrasonic treatment for 60 min. Finally, after centrifugation for 40 min, the dark green supernatant was collected to obtain the few-layer Ti3C2T x MXene nanosheets; (2) At room temperature, 12.56 mg of MXene and 10.76 mg of nanobacterial cellulose were dispersed in 20 mL of water and magnetically stirred for 30 min to form a slurry connected by hydrogen bonds. Subsequently, 100 mg of activated carbon particles were added to the obtained slurry and further stirred for 24 h to obtain a composite electrode slurry (called MX-AB). The MX-AB slurry was filtered on a filter membrane by vacuum filtration technology, freeze-dried, and cut into 1.13 cm2 pieces by a slicer. 2 MX-AB electrode membrane; (3) An aqueous solution containing 2M LiI and 0.2M I2 was used as the positive electrode electrolyte, and 56.76 μL of the positive electrode electrolyte was dropped onto the MX-AB electrode membrane. After drying at room temperature for 6 h, a high-loading composite iodine positive electrode (MX-AB@I) was obtained.

[0046] Assembly of aqueous zinc-iodine battery: The obtained MX-AB@I was used as the iodine positive electrode, 30μL 2M ZnSO4+0.1MLi2SO4 solution as the electrolyte, 20μm metal zinc sheet as the negative electrode, and glass fiber membrane as the separator to assemble an aqueous zinc-iodine battery.

[0047] Example 2

[0048] The preparation process of the high-load composite iodine positive electrode based on the MXene electrochemical reaction regulator in Example 2 includes: (1) dissolving 1 g of lithium fluoride in 15 mL of 9 M hydrochloric acid, slowly adding 1 g of MXene precursor (Ti3AlC2) powder, etching at 40° C. for 48 hours, and then washing by centrifugation 6 times to obtain a multilayer Ti3C2T x Then the multilayer Ti3C2T x The suspension was dispersed in 50 mL of deionized water and subjected to ultrasonic treatment for 60 min. Finally, after centrifugation for 40 min, the dark green supernatant was collected to obtain the few-layer Ti3C2T x MXene nanosheets; (2) At room temperature, 18.84 mg of MXene and 16.14 mg of nanobacterial cellulose were dispersed in 20 mL of water and magnetically stirred for 30 min to form a slurry connected by hydrogen bonds. Subsequently, 150 mg of activated carbon particles were added to the obtained slurry and further stirred for 24 h to obtain a composite electrode slurry (called 1.5x-MX-AB). The 1.5x-MX-AB slurry was filtered on a filter membrane by vacuum filtration technology, freeze-dried, and cut into 1.13 cm 2 1.5x-MX-AB electrode membrane; (3) An aqueous solution containing 2M LiI and 0.2M I2 was used as the positive electrode electrolyte. 85.14 μL of the positive electrode electrolyte was dripped onto the 1.5x-MX-AB electrode membrane and dried at room temperature for 6 h to obtain a high iodine loading of 23 mg cm -2 Composite iodine positive electrode (1.5x-MX-AB@I).

[0049] Assembly of aqueous zinc-iodine battery: The obtained 1.5x-MX-AB@I was used as the iodine positive electrode, 30μL 2M ZnSO4+0.1MLi2SO4 solution was used as the electrolyte, 10μm metal zinc sheet was used as the negative electrode, and glass fiber membrane was used as the separator to assemble an aqueous zinc-iodine battery.

[0050] Comparative Example 1

[0051] The preparation method of the high-loading composite iodine positive electrode in this comparative example 1 refers to that in Example 1, with the only difference being that in step (2), the amount of MXene used is 0 mg, and an AB electrode film is prepared; subsequently, an aqueous solution containing 2M LiI and 0.2M I2 is used as the positive electrode electrolyte, 56.76 μL of the positive electrode electrolyte is dripped onto the AB electrode film, and after drying at room temperature for 6 hours, a high-loading iodine positive electrode (AB@I) is obtained.

[0052] Comparative Example 2

[0053] The preparation method of the high-loading composite iodine positive electrode in this comparative example 2 refers to that in Example 1, with the only difference being that in step (2), the amount of MXene used is 6.28 mg, and a 0.5MX-AB electrode film is prepared; subsequently, an aqueous solution containing 2M LiI and 0.2M I2 is used as the positive electrode electrolyte, 56.76 μL of the positive electrode electrolyte is dripped onto the 0.5MX-AB electrode film, and dried at room temperature for 6 hours to obtain a high-loading composite iodine positive electrode (0.5MX-AB@I).

[0054] Assembly of aqueous zinc-iodine battery: The obtained 0.5MX-AB@I was used as the iodine positive electrode, 30μL 2M ZnSO4+0.1MLi2SO4 solution was used as the electrolyte, 20μm metal zinc sheet was used as the negative electrode, and glass fiber membrane was used as the battery separator to assemble an aqueous zinc-iodine battery.

[0055] Comparative Example 3

[0056] The preparation method of the high-load composite iodine positive electrode in this comparative example 3 refers to Example 1, except that: in step (2), the amount of MXene used is 25.12 mg, and a 2MX-AB electrode film is prepared. Subsequently, an aqueous solution containing 2M LiI and 0.2MI2 is used as the positive electrode electrolyte, and 56.76 μL of the positive electrode electrolyte is dripped onto the 2MX-AB electrode film, and dried at room temperature for 6 hours to obtain a high-load composite iodine positive electrode (2MX-AB@I).

[0057] Assembly of aqueous zinc-iodine battery: The obtained 2MX-AB@I was used as the iodine positive electrode, 30μL 2M ZnSO4+0.1MLi2SO4 solution was used as the electrolyte, a 20μm metal zinc sheet was used as the negative electrode, and a glass fiber membrane was used as the separator to assemble an aqueous zinc-iodine battery.

[0058] Comparative Example 4

[0059] The preparation method of the high-loading composite iodine positive electrode in this comparative example 4 refers to that in Example 2, with the only difference being that in step (2), the amount of MXene used is 0 mg, and a 1.5x-AB electrode film is prepared; subsequently, an aqueous solution containing 2M LiI and 0.2M I2 is used as the positive electrode electrolyte, 85.14 μL of the positive electrode electrolyte is dripped onto the 1.5x-AB electrode film, and after drying at room temperature for 6 hours, a high-loading iodine positive electrode (1.5x-AB@I) is obtained.

[0060] Assembly of aqueous zinc-iodine battery: The obtained 1.5x-AB@I was used as the iodine positive electrode, 30μL 2M ZnSO4+0.1MLi2SO4 solution was used as the electrolyte, 10μm metal zinc sheet was used as the negative electrode, and glass fiber membrane was used as the separator to assemble an aqueous zinc-iodine battery.

[0061] Figure 1 This is a scanning electron microscopy (SEM) image of the MX-AB electrode membrane prepared in Example 1. Figure 2 This is a digital photo of the MX-AB electrode membrane prepared in Example 1. Figure 1 It can be seen that the MX-AB electrode membrane is a porous self-supporting electrode formed by a high-conductivity MXene / bacterial cellulose mixed network formed by nanobacterial fibers and MXene nanosheets uniformly wrapping activated carbon particles. Figure 2 It can be seen that the stable interconnection between each component endows the MX-AB electrode with good mechanical flexibility, enabling it to bend without breaking.

[0062] Figure 3 The weight changes of the MX-AB electrode membrane and the MX-AB@I positive electrode membrane prepared in Example 1 before and after iodine loading. Figure 4 The thermogravimetric curves of the MX-AB electrode membrane and the MX-AB@I cathode membrane prepared in Example 1 before and after iodine loading. Figure 3 It can be seen that the actual iodine active material loading of the high-loaded MX-AB@I cathode is about 15.33 mg cm -2 This is consistent with the theoretically calculated iodine active substance loading (15.35 mg cm -2 ) is very close. And by Figure 3 It can be seen that the iodine active material content of the self-supporting MX-AB@I positive electrode is as high as about 60.43wt.%.

[0063] Figure 5 The cross-sectional SEM image of the MX-AB@I cathode prepared in Example 1 and the corresponding element distribution image. As can be seen from the figure, the thickness of the high-iodine-loaded MX-AB@I cathode is about 270 μm. The C, Ti, and I element distribution diagrams further confirm the successful loading of iodine in the cathode and the uniform distribution of each element.

[0064] Figure 7 This is a SEM image of the AB electrode membrane prepared in Comparative Example 1. As can be seen from the figure, the AB electrode membrane in Comparative Example 2 exhibits a porous network structure formed by nano-bacterial cellulose bonding activated carbon particles.

[0065] Figure 8 The conductivity of the MX-AB and AB electrode membranes prepared in Example 1 and Comparative Example 1, respectively. As can be seen from the figure, the MX-AB electrode membrane prepared in Example 1 achieved a conductivity of up to 13.57 S cm -1 The conductivity of the AB electrode film prepared in Comparative Example 1 is only about 3.66 S cm -1 From the SEM images of the MX-AB electrode in Example 1 and the AB electrode film in Comparative Example 1, it can be seen that this is because the Ti3C2T attached to the nanobacterial cellulose in the MX-AB electrode film prepared in Example 1 x MXene nanosheets act as fast and continuous electron transport pathways, enhancing the conductive contact between activated carbon particles and thus improving the overall conductivity of the composite electrode.

[0066] Combining the working principle of the battery with the UV-visible absorption spectrum testing device, the iodine positive electrodes of Example 1 and Comparative Example 1 are designed into "cuvette" type batteries, and the immobilization effects of the MX-AB@I positive electrode in Example 1 and the AB@I positive electrode in Comparative Example 1 on polyiodides are compared.

[0067] Fig. 9 In-situ ultraviolet absorption spectrum test of the "cuvette" zinc-iodine battery assembled with the MX-AB@I and AB@I positive electrode films prepared in Example 1 and Comparative Example 1. Fig. 9 As shown in a, the iodine-loaded composite positive electrode (MX-AB@I or AB@I) and the zinc metal negative electrode are placed at both ends of the "cuvette" type battery, and a 2M ZnSO4+0.1M Li2SO4 mixed solution is used as the electrolyte. The positive and negative electrodes of the "cuvette" type battery are connected to the electrochemical workstation through wires. Ultraviolet or visible light is transmitted through the other two sides of the cuvette to measure the real-time concentration of polyiodide during charging. Fig. 9 As shown in b, the absorbance of the zinc-iodine battery using the AB@I positive electrode in comparison 1 at 288 and 354 nm increases, indicating that I3 -The concentration increases rapidly. This is due to the weak interaction between activated carbon and polyiodide, which makes it easy for polyiodide to dissolve in the electrolyte, thereby increasing the peak value in the UV-visible absorption spectrum measurement. However, in the zinc-iodine battery using the MX-AB@I positive electrode in Example 1, the concentration of I3 - The associated absorption peaks remain low throughout the charging process (e.g. Fig. 9 c). It can be seen that in situ UV-visible absorption spectroscopy measurements confirmed that the MXene-functionalized composite electrode has an excellent - The fixed adsorption effect of the intermediate product can effectively inhibit the shuttling effect of polyiodide ions.

[0068] The electrochemical performance of the aqueous zinc-iodine batteries prepared in Example 1 of the present invention and Comparative Examples 1-3 was tested.

[0069] At the same high iodine loading, the coulombic efficiency ( Fig.10 ) and loop test ( Fig.10 The cycle life and reversibility of zinc-iodine batteries prepared with different iodine positive electrodes prepared in Example 1 of the present invention and Comparative Examples 1-3 are analyzed, thereby directly reflecting the multi-iodine ion shuttle effect. Fig.10 The zinc-iodine battery assembled with different iodine positive electrodes prepared in Example 1 and Comparative Examples 1-3 was operated at a current density of 0.1A. -1 Long cycle and coulombic efficiency when MXene is used. In the absence of MXene, the zinc-iodine battery assembled with the iodine cathode (AB@I) in Comparative Example 1 decays rapidly in just 40 cycles and exhibits a low average coulombic efficiency of 91.04%, which means that there is a serious multi-iodide shuttling effect. The surface capacity of the zinc-iodine battery assembled with the iodine cathode (0.5MX-AB@I) in Comparative Example 2 began to fail after 160 cycles, and the average coulombic efficiency was increased to 96.84%. However, due to the inability to adsorb enough poly-iodides at a low MXene content, the multi-iodide still undergoes a shuttling effect. In addition, the zinc-iodine battery assembled with the iodine cathode (MX-AB@I) of Example 1 of the present invention and the zinc-iodine battery assembled with the iodine cathode (2MX-AB@I) of Comparative Example 3 can reach a cycle life of 260, with average coulombic efficiencies of 97.23% and 97.14%, respectively, and capacity retention rates of 95.65% and 92.67%, respectively, showing good performance in inhibiting the shuttling of multi-iodides. The reason for the rapid capacity decay of the iodine positive electrode (2MX-AB@I) in Comparative Example 3 may be that the MXene content is too high and the adsorption force on iodine is too strong, and some iodine loses its activity due to adsorption. Therefore, too high or too low MXene content will reduce the overall performance of the battery. In the iodine positive electrode (MX-AB@I) in Example 1 of the present invention, the MXene content is 1 mg cm -2 The battery cycle stability is best under these conditions.

[0070] Using the iodine positive electrode prepared in Example 1 of the present invention and Comparative Example 1, the redox kinetics of the zinc-iodine battery was evaluated by cyclic voltammetry (CV). Fig.11 The zinc-iodine battery assembled with the MX-AB@I and AB@I positive electrodes prepared in Example 1 and Comparative Example 1 was -1 CV curves under the same conditions. Both batteries show a pair of redox peaks, showing I2 / I - Compared with the iodine positive electrode AB@I zinc-iodine battery prepared in comparative example 1, the iodine positive electrode MX-AB@I zinc-iodine battery prepared in Example 1 of the present invention has a sharper redox peak and a higher peak current density. In addition, the polarization overpotential of the MX-AB@I zinc-iodine battery is significantly lower than that of the AB@I zinc-iodine battery (124mV vs. 182mV), which indicates that Ti3C2T x MXene electrochemical reaction modifiers enhance the redox kinetics of zinc-iodine batteries.

[0071] The electrochemical performance of the aqueous zinc-iodine batteries prepared in Example 2 of the present invention and Comparative Example 4 was tested.

[0072] Fig.12 The zinc-iodine battery assembled with 1.5x-MX-AB@I and 1.5x-AB@I positive electrodes prepared in Example 2 and Comparative Example 4 was tested at 0.1A g -1 The long cycle test results under the conditions of 2.3 mA cm -2 Under the same conditions, about 4.0 mAh cm -2 Even after 200 cycles, it can still maintain about 94.4% of its initial capacity (3.77 mAh cm -2 ). In contrast, the durability of the zinc-iodine battery assembled with the iodine positive electrode (1.5x-AB@I) of Comparative Example 4 is significantly reduced. After 58 cycles under the same conditions, the capacity retention rate is only 32.9%.

[0073] More importantly, the zinc-iodine battery assembled with the iodine positive electrode (1.5x-MX-AB@I) in Example 2 of the present invention has a zinc utilization rate of 78.7% and a capacity of 171.3Wh kg -1 High energy density.

[0074] In summary, the high iodine-loaded iodine cathode provided by the present invention and the introduction of its MXene electrochemical reaction regulator solve the problems of slow kinetics and multi-iodide shuttling in high-loaded zinc-iodine batteries, which is of great significance to the performance improvement and practical application of zinc-iodine batteries.

Claims

1. A high-load composite iodine positive electrode based on MXene electrochemical reaction regulator, characterized in that: The high-load composite iodine positive electrode comprises: a porous self-supporting composite electrode film of the carbon material wrapped by a MXene / cellulose network formed by mixing MXene nanosheets, carbon material and cellulose, and an iodine active substance loaded on the porous self-supporting composite electrode film; wherein the iodine active substance comprises I - ions and I2; the MXene nanosheet is Ti3C2T x 、Nb2CT x 、Mo2CT x 、V2CT x At least one of .

2. The high-load composite iodine positive electrode based on MXene electrochemical reaction regulator according to claim 1, characterized in that: The loading of MXene on the high-loading composite iodine positive electrode is 0.7-1.8 mg cm -2 The loading amount of the iodine active substance is 10 to 25 mg cm -2 .

3. A method for preparing a high-load composite iodine positive electrode based on a MXene electrochemical reaction regulator according to claim 1 or 2, characterized in that: include: (1) mixing MXene nanosheets, carbon material and cellulose to obtain a mixed dispersion; (2) vacuum filtering and freeze-drying the mixed dispersion to obtain a self-supporting composite electrode membrane; (3) Using an aqueous solution containing an iodine active substance as a positive electrode electrolyte, dripping it onto the self-supporting composite electrode membrane, and drying it to obtain the high-load composite iodine positive electrode.

4. The preparation method according to claim 3, characterized in that: The carbon material is at least one of activated carbon, carbon nanotubes, carbon fibers, and graphene; The cellulose is at least one of plant cellulose, bacterial cellulose and microfibrillated cellulose.

5. The preparation method according to claim 3 or 4, characterized in that: In step (1), the mass ratio of the MXene nanosheets, the carbon material and the cellulose is (0.1-2):(5-10):(0.1-1).

6. The preparation method according to any one of claims 3 to 5, characterized in that: In step (2), the freeze-drying temperature is -20 to -30°C and the time is 5 to 7 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that: In step (3), in the positive electrode electrolyte, I - The ratio of the concentration of ions to I2 is (5~10):(1~5).

8. The preparation method according to any one of claims 3 to 7, characterized in that: In step (3), the drying is carried out at room temperature, and the drying time is 6 to 20 hours.

9. A zinc-iodine battery, characterized in that: The zinc-iodine battery comprises the high-load composite iodine positive electrode according to claim 1 or 2, a zinc negative electrode, a battery separator and an electrolyte.

10. The zinc-iodine battery according to claim 9, characterized in that: The thickness of the zinc negative electrode is 10 to 20 μm; The battery separator is at least one of a glass fiber separator, an aramid nanofiber separator, a non-woven fabric separator, a filter paper separator, and a polyolefin separator; The electrolyte is a mixed electrolyte containing ZnSO4 and Li2SO4; in the electrolyte, the concentration ratio of ZnSO4 to Li2SO4 is (10-20): (1-5).

Citation Information

Patent Citations

  • Electrical impedance spectrum detection system and electrical impedance spectrum detection method for crops

    CN101943672A

  • MXene-based three-dimensional porous flexible self-supporting membrane, preparation method thereof and application of membrane in electrochemical adsorption of dyes

    CN112452299A

  • High-stability zinc-iodine battery positive electrode composite material as well as preparation method and application thereof

    CN113036144A

  • Preparation method of MXene nanocellulose carbon nanotube composite material

    CN114605708A

  • Flexible self-supporting lithium-sulfur battery composite positive electrode material and preparation method thereof

    CN116487558A

Cited By

  • Aramid fiber composite pole piece and preparation method and application thereof

    CN122455961A

  • A method for preparing a high-load stable PMAAC-I composite cathode and its application

    CN122576079A

  • Preparation method and application of high-load stable PMAAC-I composite positive electrode

    CN122576079B